Quand optimiser désenchante. Les effets de la venture philanthropy sur l'engagement des volontaires en service civique - Emily Lopez Puyol; Christine Félix (Nantes Université, 2022)
The current model of priority education policies results in an individualization of the support given to students through several types of programs installed outside the traditional school setting. This outsourcing is often managed by the associative sector. This sector, increasingly confronted with the need to integrate entrepreneurial logics, apply reorganizational strategies, which are likely to go against its primary objectives. Through the case study of an association, which is complementary to public education, this article aims to analyze the effects of venture philanthropy on a system of equal education opportunities program throughthe work of volunteers in civic service within this program. Behind the objective of "optimizing" the system, the transformation of the volunteer´s work within this structure will give us an insight into the continuity of a neoliberal approach in education and its effects in the "engagement" practices which are common within the associative sector.